Cartographie diachronique de la dynamique forestière et évolution de l'invasion des subéraies et des eucalyptaies par l'Acacia noir (Acacia mearnsii De Wild) dans le Parc National d'El Kala (Nord-Est algérien) - Samir Chekchaki; Mohamed-Djalil Zaafour; Arifa Beddiar (Physio-Géo)
The Black Wattle (Acacia mearnsii De Wild) is now an integral part of the landscape of the El Kala region. Fifty years after its introduction, this Australian legume occupies more than 3200 ha and represents a major threat to local biodiversity.The present work was undertaken on the one hand, in order to ensure a sustainable management of the natural resources of the region; on the other hand, in order to develop a better understanding of the triggering mechanisms for the spread of the invasive species.The purpose of this study is to assess changes in land cover from 1959 to 2016, but also to examine the appearance, evolution and current distribution of the spots of Acacia mearnsii in two sites, using the tools of the airborne and satellite remote sensing.The results obtained show that on sites 1 (forest of Boumalek, 1536 ha) and 2 (forest of Tonga, 1690 ha), the initial plant formations, without Black Acacia, lost 708 and 581 ha respectively. The cork oak forest with undergrowth has undergone a particularly remarkable retraction (196 ha in Boumalek, 350 ha in Tonga). In almost 30 years (from 1987 to 2016), the area of invaded eucalyptus and cork oak forests increased respectively from 62 ha to 487 ha and from 0.2 to 188 ha in Boumalek, from 30 ha to 730 ha and from 1.6 to 120 ha in Tonga.During the period considered, of almost 60 years, disturbances of natural and especially anthropic origin have been aggravating factors of the invasion, by opening invasion windows and by triggering the emergence of Acacia mearnsii seeds.